Transeksi Medula Spinalis Nontraumatik Inkomplit pada Kompresi Medula Spinalis Suspek Metastasis - Veronica, Vanessa; Ardianto, Dony (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: Vertebrae are the most common sites for metastases, and spinal cord compression can be an early manifestation of malignancy. The incidence of spinal cord compression tends to increase as the survival rate of cancer patients increases. We report a case of spastic paraparesis in suspected metastatic spinal cord compression. Case presentation: A 62-year-old male presented to the emergency room complaining of weakness in lower limbs and lower back pain that began one month prior to hospital admission and progressively worsened. The patient appeared moderately ill and completely conscious, with a body temperature of 36.4Ã‚Â°C, a pulse rate of 89 beats per minute, a respiratory rate of 18 breaths per minute, oxygen saturation of 99%, a blood pressure of 144/81 mmHg, and a pain scale of 7. Neurological examination demonstrated spastic paraparesis with loss of posture and vibration sensation in both lower extremities. There were masses in the bodies of the fourth to tenth thoracic vertebrae, along with paravertebral masses and destruction of the surrounding bones, as well as intracranial and extracranial medullary invasions with lytic lesions in the second lumbar vertebra. Consolidation was also detected on radiological testing in the left lung's apicoposterior region, leading to the appearance of a pulmonary mass on computed tomography (CT) thoracolumbar myelography. Ketorolac, methylprednisolone, and citicoline were administered as therapy. Within a few days, the patient demonstrated significant relief in pain. Conclusion: Spinal cord compression due to metastases is an oncological emergency where spastic paraparesis and proprioception deficits are included as the neurologic consequences.